Structural and functional interrelations of psychological characteristics of students depending on the type of sports activity - Osipenko, Evgeny V.; Yuroshkevich, Artyom A.; Shakhov, Artem A. (Физическое воспитание и студенческий спорт)
The article studies the influence of sport games on the development of team skills and cognitive functions in students of technical university. The relevance of the study is determined by the need to identify the psychological and social effects of various types of sports activities in the conditions of an educational institution. The aim of the study is to identify structural and functional interrelationships of cognitive, emotional and social characteristics that form a multi-competence profile of students of technical specialties depending on the type of sports activity. The study involved 60 male students (2nd-4th years), distributed in four groups: basketball, volleyball, handball and training sessions in the discipline ‘Physical education’. Validated psychometric techniques were used to assess motivation, cognitive flexibility, mental toughness, team effectiveness and emotional intelligence. Such methods as descriptive statistics, correlation analysis, factor analysis, cluster analysis and regression analysis were used. It was proved that specialized sports promote the development of unique psychological profiles: basketball contribute to the development of cognitive flexibility and emotional regulation, volleyball fosters team cohesion and empathy, handball helps to develop mental strength and goal orientation. The system analysis showed that up to 62% of variation in sports performance is explained by the interaction of these characteristics. This emphasizes the need for a differentiated approach to the physical education of students in technical universities. The findings can be used to optimize physical education programs and psychological preparation of students for sports activities.